Implementasi Manajemen Kurikulum dan Penilaian SMPN 29 Jakarta - Rosyid Rosyid; Amsori Amsori; Hanafiah Hanafiah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to elaborate on curriculum implementation and assessment at SMPN 29 in Jakarta. The research method used is descriptive-qualitative. The research results show that the existence of the curriculum at SMPN 29 Jakarta is very important in the world of education because of its very strategic position in all aspects of educational activities. Based on all views from various angles regarding the notion of curriculum, the notion of curriculum can be organized into two, namely: the first curriculum is a number of content plans, which are a number of learning stages designed for students with educational institution guidelines in the form of static or dynamic processes and competencies. And secondly, the curriculum is the entire experience under the guidance and direction of the educational institution that brings it into learning conditions. The concept of curriculum and assessment at SMPN 29 Jakarta is seen as a learning plan for students or a set of goals to be achieved.